2010
DOI: 10.1017/s1047951110000727
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial rigidity in children affected by Cushing’s syndrome after successful surgical cure

Abstract: In spite of its successful surgical cure, Cushing's syndrome results in a significantly decreased arterial distensibility when compared with the control group, which might explain these differences in blood pressure levels. It underlines a significantly higher cardiovascular risk, notwithstanding both the normalisation of cortisol secretion and the very early age of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Notwithstanding this amelioration in cardiac morphology, the percentage of abnormal measurements remained in excess compared with controls, in particular relative to segmental measurements. In this context, a recent cross‐sectional study on children cured of Cushing’s syndrome revealed greater mass measurements some 4 years after surgery compared with matched controls 24 …”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding this amelioration in cardiac morphology, the percentage of abnormal measurements remained in excess compared with controls, in particular relative to segmental measurements. In this context, a recent cross‐sectional study on children cured of Cushing’s syndrome revealed greater mass measurements some 4 years after surgery compared with matched controls 24 …”
Section: Discussionmentioning
confidence: 99%
“…DBP completely normalized in all patients within 3 months [25]. In contrast, after successful treatment of 23 children with CS, an Italian study found a persistent significant impairment in arterial distensibility and altered 24-h BP monitoring, compared to controls [119]. This suggests that while BP improves faster in young patients, who are somewhat protected from microvascular damage, an increased cardiovascular risk persists despite cortisol and BP normalization.…”
Section: Effect Of Treatment Of Cushing's Syndrome On Hypertensionmentioning
confidence: 99%
“…The QKd technique has previously been validated in comparison to pulse wave velocity (19). Previous studies in pediatric patients have been performed as well (24,25). Because this interval is inversely correlated with pulse wave velocity, QKd measurement provides valuable information on arterial distensibility, as it is calculated using an arterial segment including the ascending aorta and a portion of the subclavian and brachial arteries (20).…”
Section: Introductionmentioning
confidence: 99%